Chemical composition and physicochemical properties of red seaweed (Kappaphycus alvarezii) and brown seaweed (Sargassum polycystum) from Sabah, Malaysia - Mohd Subakir, Farah Nurshahida; Hamimi, I. A.; Mohd Azman, N. A.; Zaharudin, Nazikussabah (AIP Publishing, 2023)
The proximate composition, amino acid composition and some physico-chemical properties of two type of seaweeds Kappaphycus alvarezii and Sargassum polycystum which widely cultivated in Sabah, Malaysia were investigated. S. polycystum showed the highest level of protein and crude fibre with 11.69% and 39.863% dry weight, respectively. Minor component was fat 0.12-0.13% in both seaweeds. As for the physicochemical properties of the seaweeds, their swelling capacity (SWC) ranged from 13.33 to 35.83 mL/g while water retention capacity (WRC), and oil retention capacity (ORC) ranged from 8.18 to10.59 g/g dry weight and 2.68 to 3.32 g/g dry weight, respectively. SWC and ORC of K. alvarezzi was higher than S. polycystum (p<0.05). Both seaweeds contained high amounts of minerals and balanced amino acid profiles. This study suggested that K. alvarezzi has high nutritional value which could be potentially used as ingredients in human food application.